2013
DOI: 10.1097/aln.0b013e3182834d77
|View full text |Cite
|
Sign up to set email alerts
|

Selective Anesthesia-induced Neuroinflammation in Developing Mouse Brain and Cognitive Impairment

Abstract: Background Recent population studies have suggested that children with multiple exposures to anesthesia and surgery at an early age are at an increased risk of cognitive impairment. We therefore have established an animal model with multiple versus single exposures of anesthetic(s) in young versus adult mice, aiming to distinguish the role of different anesthesia in cognitive impairment. Methods Six day and 60 day-old mice were exposed to various anesthesia regimen. We then determined the effects of the anes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
358
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 350 publications
(381 citation statements)
references
References 69 publications
20
358
1
2
Order By: Relevance
“…2011; Murphy and Baxter 2013; Shen et al. 2013a). A majority of the human studies were conducted with a retrospective population cohort approach, by gathering data from a specific subpopulation and identifying incidences of general anesthetic exposure before the ages of 3–6.…”
Section: Introductionmentioning
confidence: 99%
“…2011; Murphy and Baxter 2013; Shen et al. 2013a). A majority of the human studies were conducted with a retrospective population cohort approach, by gathering data from a specific subpopulation and identifying incidences of general anesthetic exposure before the ages of 3–6.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that sevoflurane, the most commonly used anesthetic in children, can induce apoptosis, increases in β-amyloid levels, and neuroinflammation in the brains of fetal mice and caused learning and memory impairment 3 weeks later (Shen et al, 2013;Zhang et al, 2013a,b). Clinical studies have also found that children with multiple exposures to general anesthesia and surgery at an early age may develop learning disabilities (Sun, 2010;Flick et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The temperature of the anesthetizing chamber was controlled to maintain a rectal temperature of 37° ± 0.5°C in the mice. Previous studies (Shen et al, 2013;Zhang et al, 2013a,b) have shown that anesthesia with 3% sevoflurane for two hours did not significantly change the values of pH, partial pressure of oxygen, or partial pressure of carbon dioxide in anesthetized mice compared with the control group. Furthermore, compared with control mice, the anesthetized mice did not show significant changes in behavior after anesthesia (e.g., eating, drinking, general activity, and body weight).…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sevoflurane is an inhaled anesthetic commonly used in the clinic, particularly in pediatric medicine, due to its minimal airway reactivity and low blood/gas partition coefficient (5). Previous studies have indicated that sevoflurane causes biochemical changes, including apoptosis, amyloid-β accumulation and neuroinflammation in the hippocampus or cortex, and induces hippocampus-dependent and -independent cognitive dysfunction in developing mice (4,6,7). However, its underlying mechanisms of action remain unknown.…”
Section: Introductionmentioning
confidence: 99%